Biology and life table of Eotetranychus lewisi (Acari: Tetranycidae) on Prunus persica cultivars from the Ecuadorian Andean region - Miño, César; Santana, Rita; León, Olguer; Colmenárez, Yelitza [UNESP]; Villa-Murillo, Adriana; Vásquez, Carlos (Taylor & Francis, 2022)
Eotetranychus lewisi (McGregor) is an important pest mite found in peach crops. This pest has recently been reported in the province of Tungurahua, Ecuador, little information is available. The biology and life table of E. lewisi using three peach cultivars (Zapallo, Blanco Abridor, and Tejón) was evaluated under laboratory conditions (19°C, 45% R.H., and 12:12 L.D). Mites were collected from Euphorbia pulcherrima growing at the Faculty of Agricultural Sciences, Technical University of Ambato. The mites were able to grow through the immature phase of the Blanco Abridor and Tejón cultivars. The mean duration of the immature phase (egg to adult) did not show significant differences between the Blanco Abridor and Tejón cultivars, ranging from 16.24 to 16.56 days. The mean female fecundity reared on Tejón was 18% higher than on Blanco Abridor, though their longevity was similar on both. The mean net reproductive rate (R0) was higher on Tejón (61.25), suggesting that more females will be born when the mites are raised on this cultivar. Based on our results, Tejón and Blanco Abridor were susceptible to E. lewisi; while, the mites could not reach adulthood on Zapallo, suggesting at least some resistance mechanisms, however more detailed studies are required.  .
Keywords: biology; cultivars; fecundity; peach; Tetranychidae; Tungurahua